2004
DOI: 10.1007/s00424-004-1330-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonic anhydrase inhibition on GFR and renal hemodynamics in adenosine-1 receptor-deficient mice

Abstract: The reduction of glomerular filtration rate (GFR) caused by inhibitors of carbonic anhydrase (CA) is thought to be initiated by activation of the tubuloglomerular feedback (TGF) mechanism. We determined the effect of the CA inhibitor benzolamide (Bz) on renal hemodynamics in adenosine-1 receptor (A1AR) knockout mice that have been shown previously to lack a TGF response. In A1AR(+/+) mice, Bz (150 microg plus 2 microg/min) reduced RBF by 19.8% (from 829+/-42 to 666+/-44 microl/min; n=7), and GFR by 19.8% (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
3
11
1
Order By: Relevance
“…An earlier study demonstrated that the CAI benzolamide induced a similar magnitude decrease of GFR and RBF in both A1ARϪ/Ϫ knockout and wild-type mice, despite the absence of TGF responses in the A1ARϪ/Ϫ knockout mice (Hashimoto et al, 2004a). Our data, using pharmacological blockade of A1AR, are consistent with these findings.…”
Section: A1 Receptor Blockade and Carbonic Anhydrase Inhibition 535supporting
confidence: 82%
See 3 more Smart Citations
“…An earlier study demonstrated that the CAI benzolamide induced a similar magnitude decrease of GFR and RBF in both A1ARϪ/Ϫ knockout and wild-type mice, despite the absence of TGF responses in the A1ARϪ/Ϫ knockout mice (Hashimoto et al, 2004a). Our data, using pharmacological blockade of A1AR, are consistent with these findings.…”
Section: A1 Receptor Blockade and Carbonic Anhydrase Inhibition 535supporting
confidence: 82%
“…Our renal hemodynamic data in rats obviously differ from that of Hashimoto et al (2004a) in mice. However, our results are in general agreement with Deng et al (2002), who reported that in the rat, angiotensin-converting enzyme inhibitor treatment did not block the RBF decrease induced by benzolamide.…”
Section: A1 Receptor Blockade and Carbonic Anhydrase Inhibition 535contrasting
confidence: 41%
See 2 more Smart Citations
“…It was observed, however, that the absence of a functional TGF mechanism did not prevent the reduction in GFR or renal blood flow caused by carbonic anhydrase inhibition. On the other hand, acute angiotensin II receptor blockade diminished the effect of carbonic anhydrase inhibition on GFR and renal blood flow in either genotype (119). The authors concluded that TGF activation is not necessary for the decline in GFR caused by carbonic anhydrase inhibitors and that the GFR reduction appears to be the consequence of a combination of an angiotensin II-dependent reduction in renal plasma flow and a diuresis-induced increase in P PT .…”
Section: Absence Of Tgf Response In Adenosine a 1 Receptor-deficiementioning
confidence: 96%